A missense GATA3 mutation, Thr272Ile, causes the hypoparathyroidism, deafness, and renal dysplasia syndrome. - Gaynor, K; Grigorieva, I; Nesbit, M; Cranston, T; Gomes, T; Gortner, L; Thakker, R (2009)
CONTEXT: The hypoparathyroidism, deafness, renal dysplasia (HDR) syndrome is caused by mutations in the gene encoding GATA3, which belongs to a family of dual zinc-finger transcription factors that have a role in vertebrate embryonic development. OBJECTIVE: The aim of the study was to identify the GATA3 mutation in a HDR patient and determine its functional consequences. PATIENT AND DESIGN: A patient with HDR was studied after approval from the local ethical committee. Leukocyte DNA was used with GATA3-specific primers for PCR amplification, and the DNA sequences of the PCR products were determined. Wild-type and mutant GATA3 constructs were transfected into COS-7 cell, and their functions were assessed by Western blot analysis, immunocytochemistry, EMSAs, luciferase reporter assays, and three-dimensional modeling. RESULTS: A novel missense mutation, Thr272Ile, in zinc finger 1 (ZnF1) of GATA3 was identified. Western blot analysis and immunofluorescence revealed that the mutation did not affect nuclear localization of GATA3. However, EMSAs showed it to reduce DNA binding affinity, but not stability, and yeast two-hybrid assays demonstrated that the mutant GATA3 resulted in a loss of interaction with ZnF1 and ZnF6 of the cofactor FOG2. The mutant GATA3 significantly reduced luciferase reporter activity by more than 65% (P < 0.001), and three-dimensional modeling indicated that the functional abnormalities may be due to a loss of Thr272 polar side chain interaction with Leu268. CONCLUSIONS: A novel missense HDR-associated GATA3 mutation, Thr272Ile, has been identified and shown to result in reduced DNA binding, a partial loss of FOG2 interaction, and a decrease in gene transcription.